(untitled) (LEARNing Landscapes, 2013)
Using autobiographical narrative inquiry (Connelly & Clandinin, 1990), I inquire into my experiences as a teacher, beginning with an inquiry into my early experiences on home and school landscapes. I explore my teacher stories to live by (Connelly & Clandinin, 1999) and inquire into how my stories have shifted and changed, over time and place. As I explore the bumping places and tensions I experience as teacher, my purpose is to show the ways I learned to attend to children’s familial curriculum-making worlds (Huber, Murphy, & Clandinin, 2011). In doing so I offer a possible counter narrative of curriculum making in schools, which honors and validates children’s stories of experiences lived and told in homes and communities.